Government Intelligence as A New Branch of Government Studies - Zainal, Irhamni (Green Publisher Indonesia, 2024)
The discussion of government is deeply intertwined with the Science of Government itself, tracing back centuries to classical government science and evolving into contemporary forms. Within government implementation, symptoms, actions, and events constitute its essence. Symptoms signify its existence, actions denote activities by government entities to serve public welfare, and events encapsulate official government activities recorded as historical records. These components collectively aim to establish order, peace, and societal well-being. Government actions and events often exhibit intelligence in various forms, including information, administrative products, and activities. For instance, the reliance on accurate data and facts in decision-making processes underscores the importance of intelligence in governance. Effective public policies should be grounded in credible information that addresses societal needs and garners support. Information, data, and facts serve as vital elements in policymaking and governance, contributing significantly to leadership processes. Recognizing this, there's a burgeoning field termed Government Intelligence, aimed at furthering the understanding and utilization of intelligence in governmental practices. This paper serves as an inaugural step in developing Government Intelligence, offering practical insights for governmental practices at all levels. It underscores the importance of early vigilance tasks and national unity in governance. While acknowledging its limitations, the author invites feedback and suggestions to enhance the content, fostering the growth and refinement of this emerging field of study.